Dynamical Properties of the New Ternary Fission in Collisions of 197Au+197Au at 15 MeV/Nucleon - Xian Li; Chengqian Wang; Yaohui Xu (International Journal of Photoenergy)
The dynamical properties of the new ternary fission in heavy 197Au+197Au at 15 MeV/nucleon have been investigated by using the improved quantum molecular dynamics model. The dependencies of the production probability, lifetime, the time interval, and angular distribution on the impact parameter are carefully studied. The calculation results show that the characteristics of these are very different between the small and the large impact parameter. Comparing the theoretical results with the experimental data, one can obtain that the fast ternary breakup likely occurs at the impact parameter region b=7‐9 fm. The nonisotropic of angular distribution and the short time interval among two fissions indicates that the fast ternary fission is a nonequilibrium and violent process.